النمذجة بمساعدة الحاسوب للحالة الديناميكية العابرة لميكانيزم الرفع في رافعة ودراسة تأثير المميزات الميكانيكية الستاتيكية لنظام القيادة الكهربائية على المعامل الديناميكي لميكانيزم الرفع - سمير نمر كـفا; كارلـو مقدسـي (Tishreen University, 2019)
يعتبر تطوير الطرق التصميمية من المسائل الهامة ويرتبط بتطوير المبادئ النظرية الأولية في أتمتة التصاميم وإدخال علوم الحاسوب وهذا بدوره يحدد نتائج تطور عمل وإنشاء المعدات والآلات.  لذلك هدفت هذه الدراسة إلى تطوير نمذجة حاسوبية لدراسة العمليات الانتقالية العابرة على ديناميكية ميكانيزم الرفع في رافعة حيث تفترض دراسة الحمولات الديناميكية النظرية إما ثبات سرعة الرفع أو الأخذ بعين الاعتبار المميزات الميكانيكية الستاتيكية لمحرك الإدارة وذلك من خلال إعداد النماذج الرياضية التي يتم وضعها وتوصيفها بواسطة جملة معادلات تفاضلية عادية واستخدام طرق التكامل العددي على نموذج الحالة الديناميكية العابرة في ميكانيزم الرفع في الرافعة. وجدير بالذكر أن البحث هو عبارة عن مساهمة في إطار تطوير التصاميم من خلال نمذجة حاسوبية للحالة الديناميكية العابرة التي تنشأ أثناء عمل ميكانيزم الرفع في رافعة وتقييمها حتى يستطيع المصمم استنتاج النتائج الخطيرة لنشوئها وفهمها ليتمكن من السيطرة عليها والتحكم بها. The development of designing methods is considered one of the most important subjects connected to the improvement of the essential theoretical principles of automation designs and introducing computing sciences that, by their turn, specify the results of developing the function and the structure of machines and mechanisms. This study aims at enhancing the computing simulation for analyzing the passing process of the dynamics of hoisting mechanism in a crane. The study of theoretical dynamic loads assumes the stability of hoisting velocity (constant speed), or takes into consideration the static mechanical characteristics of the driving motor, by preparing the mathematical modeling of dynamic passing process of hoisting mechanism in a crane, and making simulation of all systems in a simple and accurate way. This research is a contribution of design improvement by using a new simulating method of the dynamic passing process which is produced through the work period of hoisting mechanism in a crane. This method gives the valuations of all passing processes, so the designer can deduce the serious results of their occurrence besides controlling and eliminating them. All the results of the previously study are essential steps for enhancing the hoist mechanism analysis in addition to the dynamic processes, that are related to other steps from which we can have new results too. These results help to simplify the design and analyzing all hoisting mechanism.